IMPLEMENTASI PROGRAM KELUARGA HARAPAN TERHADAP PENINGKATAN KESEJAHTERAAN MASYARAKAT MISKIN DI KECAMATAN TELLU LIMPOE KABUPATEN SIDENRENG RAPPANG - Nisra Nisra; Andi Uceng; Sapri Sapri; Syahrir L (JIA: Jurnal Ilmiah Administrasi, 2021)
The purpose of this study was to determine the impact of the implementation of the policy of the hopeful family program on improving the welfare of the poor in Tellu Limpoe District, as well as the factors that influence the impact of the policy of the hopeful family program on the improvement of the welfare of the poor. in the District. Tellu Limpoe. The population in this case is 1049 people, while the sampling used is non-probability sampling using quantitative descriptive research and data collection includes observations, interviews, documentation, questionnaires, and literature studies. The data analysis method used is data quality test, regression method and hypothesis testing and sakalalikert using a frequency table. The results showed the implementation of the policy of the family program of hope to improve the welfare of the poor in Tellu Limpoe District, Sidenreng Rappang Regency with a value of 77.8% in the good category, while factors that influence the implementation of the policy of the family program of hope to improve the welfare of the poor in Tellu Limpoe District 60.4%. The implementation of the Hope Family Program policy has a significant effect of 60.4% on the welfare of the poor in Tellu Limpoe District, Sidenreng Rappang Regency.